Economic aspects of quality of life of Bangladeshi construction workers in Malaysia - Norizan, Abdul Ghani; Md Wahidul, Haque (2020)
Quality of Life (QoL) measures provide a sense of how people's lives are going through the activities and interactions between their circumstances and psychological resources. This measurement/ evaluation is a valuable tool and a precondition for planning to improve the socio-economic QoL or Wellbeing of the people surveyed. Researchers conducted a qualitative study to know the economic QoL of Bangladeshi migrant construction workers in Terengganu, who have immigrated for less than ten years in Malaysia. Researchers triangulated the survey by two focus group discussions, 19 in-depth interviews, and observations of four spots. The research used Atlas ti to conduct the thematic analysis of the primary data. The result of the study shows that the workers are mostly in adverse QoL with the effect of freedom, functioning, facilitator, and financial management. The study finally recommends, Community-based work permit, trade union, and digital financial system toensure more freedom to improve the economic QoL of the migrant Bangladeshi construction workers.